Diagnosis and treatment of deep pyoderma in a Maine Coon cat - Damhuri, Dedi; Wibowo, Sarwo Edy; Syarifuddin, Ahmad; Safitri, Jessica Anggun; Insulistyowati, Ani; Ningsih, Amelia Tri; Jessica Anggun Safitri (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2024)
Pyoderma is a condition caused by a bacterial infection that affects the skin and has the potential to cause systemic infection. A Maine Coon cat was reported to have an open wound on its tail that was wet and oozing fluid, with the cat frequently biting and scratching the affected area. Based on the anamnesis, physical examination, and clinical symptoms, the Maine Coon cat was diagnosed with deep pyoderma. The treatment administered included antibiotics, vitamins, anti-inflammatory drugs, and antifungals. The cat underwent therapy for 30 days, showing signs of healing as the wound began to dry, although it had not yet fully closed. Supportive therapy with vitamins was continued to promote significant recovery. It was concluded that the treatment of deep pyoderma in the Maine Coon cat resulted in wound drying by day 30.